The Influence Of Animated Video “Dokter Gigi Kimi” On Improving Children’s Toothbrushing Skills - Zalfa Alzena; Tri Hartiti; Hayyu Failasufa (Universitas Muhammadiyah Semarang, 2024)
Dental and oral health problems are caused by a lack of individual understanding of dental and oral health. Efforts to prevent and care for teeth and mouth through health education, to change behavior into healthy behavior. This study aims to determine the effectiveness of the animated video Dentist Kimi’s animated Videos on toothbrushing practices. This type of research was Quasi Experimental, with a Single Group Interrupted Time-Series Design research design. The population in this study were class III students at SDN Tandang 04 Semarang aged 8-9 years, the sample in this study was 56 students. Data collection used questionnaires and observation sheets. The results of research on knowledge before education showed that the mean score (17.71) was smaller than after education (19.61) and the practice of brushing teeth before education had a mean score (11.55) which was smaller than the mean score on day 7 (14.295). , 14th day (17,091), and 21st day (19,622). Based on the results of the Paired Sample T-Test, there were differences in the mean values of knowledge and practice of brushing teeth before and after being given education for 21 days. The conclusion of this research is that education using animated video media is effective in increasing knowledge and practice of brushing teeth.